Valuing Public Investments to Support Bicycling - Thomas Götschi; Beat Hintermann (Swiss Journal of Economics and Statistics, 2014)
We develop a framework for assessing the net benefits of investments to promote bicycling, which explicitly accounts for internal costs of bicycling. We apply our model to eight Swiss cities using data from the Swiss national travel survey and find that increasing the level of bicycling by reducing internal costs leads to inframarginal benefits that exceed the net benefits from the additional bicycling. We further find that Swiss cyclists only partially internalize health benefits, which affects the benefits from infrastructure investments but also implies that there is scope for "soft" measures that would inform users about health benefits of bicycling.
Keywords: H43; H76; Q51; R41; R42; 330; Cost-benefit analysis; health impact assessment; bicycle; valuation; internal cost; health benefit; VSL